Cold and Touch Stimulation For The Assessment of Block Level At Spinal Anesthesia - Beştaş, Azize; Erhan, Ömer Lütfi; Okuducu, Mehmet Nihat; Avcı, Levent; Yaşar, Mehmet Akif (Fırat University, 2007)
Objective: To determine the dermatomal level of sensory block after spinal anesthesia traditionally used method is pinprick test. Pinprick test is an invasive and painful method. We aimed to compare the dermatomal levels of sensory block determined by noninvasive simple tests touch and cold sense loss with routinely used invasive pinprick stimulation test in clinical practice. Materials and Methods: Spinal anesthesia was performed with the patients placed in the sitting position by injecting 1 mg kg-1 2 % lidocaine intrathecally through a 22 gauge needle inserted at the L3-4 interspace. Spinal anesthesia was performed with the patients 1 2 % lidocaineplaced in the sitting position by injecting 1 mg kg intrathecally through a 22 gauge needle inserted at the L3-4 interspace. The levels of block were assessed at 5th and 20th min after the spinal injection. Needle for pinprick, a piece of cotton for touch and ice in a finger of surgical glove for cold sensory were used. Results: No significant difference was observed between the dermatomal level of loss of pinprick sense and the dermatomal level of loss of either touch sense or cold sense at 5th min. However at 20th min the dermatomal level of loss of touch sense was significantly lower than the dermatomal level of loss of pinprick and cold sensations (p

Amaç: Spinal anesteziden sonra duyusal bloğun dermatomal seviyesini belirlemek için geleneksel olarak pinpirick testi kullanılır. Pinpirick testi invazif ve ağrılı bir yöntemdir. Klinik pratikte rutin olarak kullanılan invazif pinpirick uyarısı ile nonivazif basit dokunma ve soğuk duyu kaybı testleriyle belirlenmiş duyusal blok dermatomal seviyelerini karşılaştırmayı amaçladık. Gereç ve Yöntem: Alt abdominal veya alt ekstremite cerrahi geçiren, 32 yetişkin erkek hasta (ASAI-II, 45±8 yaşlarında) bu randomize, prospektif çalışmaya alındı. Oturur pozisyonda, 1 mg kg-1 %2'lik lidokainin 22 gauge iğne ile L3-4 aralıktan enjeksiyonuyla spinal anestezi gerçekleştirildi. Spinal enjeksiyondan sonra 5. ve 20. dak.'da blok seviyeleri değerlendirildi. Pinpirick için iğne, dokunma duyusu için pamuk parçası ve soğuk duyusu için bir cerrahi eldiven parmağına konulan buz kullanıldı. Bulgular: Pinpirick duyu kaybının dermatomal seviyesi ile dokunma veya soğuk duyu kaybının dermatomal seviyeleri arasında 5. dak.'da anlamlı fark bulunmadı. Ancak, 20. dak'da dokunma duyu kaybının dermatomal seviyesi pinpirick ve soğuk duyu kaybının dermatomal seviyelerinden anlamlı derecede daha düşüktü (p
Spinal anestezide blok seviyesinin belirlenmesinde soğuk ve dokunma stimulasyonu